Perception of Nursing Educators and Students About Field Trip as a Teaching Method in Community Health Nursing - Mohamed, Ahlam Mahmoud; Elkaluby, Eman Ahmed (International Journal For Research In Health Sciences And Nursing, 2017)
Background: Varieties of teaching methods play an important role in nursing students’ acquisition of competencies during their clinical rotations. Field trip is a visit to a place outside the lecture halls which is designed to achieve certain objectives, which cannot be achieved by using other means. Aims: to determine nursing educators and students’ perception about field trip as a teaching method in community health nursing & assess for the causes behind students’ high absence during field trips Study Design: Descriptive design was used to carry out this study. Study setting: The study was conducted at the Faculty of Nursing, Alexandria University. Study tools: Three tools were used for data collection namely: Tool I: Students’ Field Trip experience assessment Questionnaire, Tool II: Nursing Students’ Field Trip Perception Assessment Questionnaire and Tool III: Nursing educators’ Field Trip Perception Assessment Questionnaire. Study subjects: consisted of 218 undergraduate nursing students and 22 community health nursing educators. Results: Only 6% of the students had attained all the visits without absenteeism. There were a lot of reasons behind the students’ high absence as receiving negative impression from their colleagues about worthlessness of the field trip, unavailability of method of transportation for far trip sites and contradicting time of visit with their working shifts at private hospitals. Moreover, there is a significant relation between nursing educators’ and students’ perceived value of field trips and community health nursing curriculum, learning process (effective learning), students’ skills development and the beneficial for the community and nursing profession. Conclusion : Nursingstudents and nursing educators had perceived positive value regarding field trips benefits to community and nursing profession, students’ skills development, learning process and finally to nursing curriculum. Moreover, the value of field trip to community and nursing profession were the most valued category rated by both undergraduate nursing students and their nursing educators. While, the least valued category, rated by both nursing students and their nursing educators, was the value of field trip to nursing curriculum. Recommendations: Enhance students’ high attendance through their motivation for example the nursing educators can offer special certificate for the highest attendance, moreover utilize new technology as recoding films, live videos to confront several barriers as environmental related barriers.